Transformation of Education Management Based on Artificial Intelligence in Enhancing Learning Effectiveness in the Era of Society 5.0 - Arman Paramansyah (PT. Hafasy Dwi Nawasena, 2026)
The transformation of education management in the era of Society 5.0 requires the integration of advanced technologies such as Artificial Intelligence (AI) to enhance learning effectiveness and institutional performance. This study aims to analyze how AI-based education management transformation contributes to improving learning effectiveness through institutional, pedagogical, and ethical dimensions. This research employs a qualitative approach with a descriptive-analytical design using a literature-based method. Data were collected from relevant scholarly journal articles and analyzed using content and thematic analysis to identify patterns, relationships, and key findings related to AI implementation in education. The results indicate that AI significantly improves curriculum relevance, administrative efficiency, teacher performance, and personalized learning processes. AI also enhances student engagement and supports the development of 21st-century skills. However, challenges such as digital inequality, limited human resource readiness, and ethical concerns related to data privacy remain critical issues. The discussion highlights that the successful implementation of AI in education depends on strong policy support, continuous teacher training, and the establishment of clear ethical guidelines. In conclusion, AI-based education management transformation can effectively enhance learning outcomes in the Society 5.0 era when implemented through a balanced, human-centered, and well-regulated approach.